The chemistry and biochemistry of partially reduced oxygen species - Koppenol, Willem (Henry Stewart Talks, 2007)
Oxy radicals and peroxides: superoxide, hydrogen peroxide, hydroxyl, peroxynitrite, Generation by ionizing radiation and by flash photolysis, Reactivity, Thermodynamics, electrode potentials and kinetics, Fenton chemistry
Archived at 2018/05/31